Cora Du Bois : Anthropologist, Diplomat, Agent - Seymour, Susan C. (Susan Christine), 1940- (Book collections on Project MUSE., 2015)
Although Cora Du Bois began her life in the early twentieth century as a lonely and awkward girl, her intellect and curiosity propelled her into a remarkable life as an anthropologist and diplomat in the vanguard of social and academic change. Du Bois studied with Franz Boas, a founder of American anthropology, and with some of his most eminent students: Ruth Benedict, Alfred Kroeber, and Robert Lowie. During World War II, she served as a high-ranking officer for the Office of Strategic Services as the only woman to head one of the OSS branches of intelligence, Research and Analysis in Southeas.